The Forests of Saurashtra - Desai, H. R. (Indian Forester, 1954)
Saurashtra has 925 sq. miles, i.e., only 4.3% of its total land area under forests. Owing to past mal-treatment the forests are very open. 500 sq. miles of forest comprising most of the reserved area belong to the Tropical Dry Mixed Deciduous type, with preponderance of teak. These are worked under regular working plans. The rest belong to the 'Tropical Thorn' type. It is intended to increase the percentage of forests to 12%. The Gir forests of Saurashtra are the last home of the Asiatic Lion which is under special protection. Its present number, as per Census taken in 1950, is 227.